Answer: w = 4 and l = 12
Step-by-step explanation:
Answer:
You will circle the second, the third and the fourth answer: 4, 5, and 9 gallons.
Step-by-step explanation:
Milk=$3.29
4x3.29= 13.16
5x3.29= 16.45
9x3.29= 29.61
Answer:
p>-1 or p<-19
Step-by-step explanation:
4p-10<6p-8 (add 10 to each side)
4p< 6p+2 (subtract 6p from each side)
-2p<2 (divide by -2 and switch the sign)
p>-1
10p+16<9p-3 (subtract 16 from each side)
10p<9p+-19 (subtract 9p from each side)
p<-19
Answer:
<h2>x = -4 or x = -2</h2>
Step-by-step explanation:
![f(x)=(x^2+6x+8)(x^2+6x+13)\\\\f(x)=0\iff(x^2+6x+8)(x^2+6x+13)=0\iff\\x^2+6x+8=0\vee x^2+6x+13=0\\\\x^2+6x+8=0\\x^2+4x+2x+8=0\\x(x+4)+2(x+4)=0\\(x+4)(x+2)=0\iff x+4=0\ \vee\ x+2=0\\x+4=0\qquad\text{subtract 4 from both sides}\\\boxed{x=-4}\\x+2=0\qquad\text{subtract 2 from both sides}\\\boxed{x=-2}\\\\x^2+6x+13=0\qquad\text{subtract 13 from both sides}\\x^2+6x=-13\\x^2+2(x)(3)=-13\qquad\text{add}\ 3^2=9\ \text{to both sides}\\x^2+2(x)(3)+3^2=-13+9\qquad\text{use}\ (a+b)^2=a^2+2ab+b^2\\(x+3)^2=-4](https://tex.z-dn.net/?f=f%28x%29%3D%28x%5E2%2B6x%2B8%29%28x%5E2%2B6x%2B13%29%5C%5C%5C%5Cf%28x%29%3D0%5Ciff%28x%5E2%2B6x%2B8%29%28x%5E2%2B6x%2B13%29%3D0%5Ciff%5C%5Cx%5E2%2B6x%2B8%3D0%5Cvee%20x%5E2%2B6x%2B13%3D0%5C%5C%5C%5Cx%5E2%2B6x%2B8%3D0%5C%5Cx%5E2%2B4x%2B2x%2B8%3D0%5C%5Cx%28x%2B4%29%2B2%28x%2B4%29%3D0%5C%5C%28x%2B4%29%28x%2B2%29%3D0%5Ciff%20x%2B4%3D0%5C%20%5Cvee%5C%20x%2B2%3D0%5C%5Cx%2B4%3D0%5Cqquad%5Ctext%7Bsubtract%204%20from%20both%20sides%7D%5C%5C%5Cboxed%7Bx%3D-4%7D%5C%5Cx%2B2%3D0%5Cqquad%5Ctext%7Bsubtract%202%20from%20both%20sides%7D%5C%5C%5Cboxed%7Bx%3D-2%7D%5C%5C%5C%5Cx%5E2%2B6x%2B13%3D0%5Cqquad%5Ctext%7Bsubtract%2013%20from%20both%20sides%7D%5C%5Cx%5E2%2B6x%3D-13%5C%5Cx%5E2%2B2%28x%29%283%29%3D-13%5Cqquad%5Ctext%7Badd%7D%5C%203%5E2%3D9%5C%20%5Ctext%7Bto%20both%20sides%7D%5C%5Cx%5E2%2B2%28x%29%283%29%2B3%5E2%3D-13%2B9%5Cqquad%5Ctext%7Buse%7D%5C%20%28a%2Bb%29%5E2%3Da%5E2%2B2ab%2Bb%5E2%5C%5C%28x%2B3%29%5E2%3D-4%3C0%5Cqquad%5Cbold%7Bno%5C%20solution%7D)
Answer:
y x (2x +y) x (7x +y)
Step-by-step explanation:
14x^2y + 9xy^2 +y^3
(Factor the expression)
y x (14x^2 +9xy +y^2)
(Rewrite the expression)
y x (14x^2 + 7xy +2xy +y^2)
(Factor the expression)
y x (7x x(2x +y) + y x (2x +y) )
(Factor the expression)
y x (2x +y) x (7x +y)
:))